The synthesis and characterisation of high performance electrode materials for Li-ion batteries - Clark, S (2017)
With the worlds demand for electricity constantly growing, energy storage technologies, and lithium-ion batteries in particular, are becoming increasingly important. One of the most significant issues concerning Li-ion batteries is that of safety. Graphite is the most commonly used anode material, however, due to its very low operating voltage vs Li+/Li0, reactive lithium can plate on the electrode surface, this is especially an issue for large batteries for use in electric vehicles. It would be useful to have an anode that operates at a higher voltage than graphite, but not at such a high voltage as to limit the overall potential of the cell. To this end the focus of this thesis is the development of an anode material that operate at 1 V vs Li+/Li0. The lithium metal sulphides have previously demonstrated that they reversibly intercalate lithium at ∼ 1 V, but the reported performance is poor. Here LiVS2 is reinvestigated and optimised to display significantly improved electrochemical properties. At a rate of 100 mAg-1 a reversible capacity of over 200 mAhg-1 is achieved compared to less than 150 mAhg-1 previously reported, capacity retention is also considerably enhanced. LiVS2 deintercalates Li+ at the high voltage of 1.3 V, therefore attention is turned to LiV0.5Ti0.5S2 which intercalates Li+ at 0.9 V and deintercalation occurs at 0.9 V. The performance of LiV0.5Ti0.5S2 is optimised and the electrochemical process by which LiV0.5Ti0.5S2 operates is fully investigated. LiV0.5Ti0.5S2 displays a low irreversible capacity loss, low polarisation, good rate capabilities and good capacity retention. As LiV0.5Ti0.5S2 operates at ∼ 1 V higher than graphite it is important to match it with a high voltage cathode so the overall potential of the cell is not significantly reduced. The lithium rich mixed metal oxides have been the focus of much research over the last 15 years and here they are investigated using a resorcinol-formaldehyde gel synthesis. 0.5Li2MnO3:0.5LiNi0.5Mn0.5O2 and 0.6Li2MnO3:0.4Li(Ni1/3Mn1/3Co1/3)O2 are both successfully synthesised and demonstrate excellent electrochemical performance. The specific capacities and capacity retention of both materials at a rate of 150 mAg-1 are excellent and better than virtually all previously reported materials of this type. Neutron diffraction was carried out on both materials to monitor structural changes on cycling. Finally, LiV0.5Ti0.5S2 and the lithium-rich mixed metal oxides are combined in full 'rocking- chair' lithium-ion cells to successfully show that both materials can be used in practical lithium-ion batteries.